In-School Sustainability Action: Climate Clever Energy Savers. (28th January 2016) - Buchanan, John; Schuck, Sandy; Aubusson, Peter
Abstract: The mandate for living sustainably is becoming increasingly urgent. This article reports on the Climate Clever Energy Savers (CCES) Program, a student-centred, problem- and project-based program in New South Wales, Australia, aimed at enabling school students to identify ways of reducing their schools' electricity consumption and costs. As part of the program, students apply for Department of Education and Communities funds to address issues of electricity usage, such as building or appliance modifications, or education campaigns. In particular, this article focuses on the systemic approach used to assist teachers and students in meeting the aims of the CCES program, the Sustainability Action Process (SAP). To ascertain the contribution and value of such a framework in achieving project outcomes and associated learning and attitudinal change, we investigated teachers' and some students' uses and opinions of the SAP via surveys ( n = 434), 16 interviews, and analysis of documents such as student work samples and lesson outlines. Our research indicates that the SAP has been a highly effective, enabling and engaging tool in helping students to identify ways and means of reducing electricity consumption and evaluating their effectiveness, as well as identifying allies and other sources of assistance in carrying out their projects.